The Role Of Digital Marketing In Promotional Strategies In Pia Village, Gempol District, Pasuruan Regency - Nikmatul Zuhro; Triana Setiyarini (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aim s to determ ine the im plem entation of promotional strategies using digital marketing for SMEs in Pia Village, as well as knowing the benefits and obstacles in im plem enting digital m ark eting as a prom otional strate gy for SMEs in Pia Village. The method used in this research is descriptive qualitative, collecting data b y conducting observations, in-depth interviews, and documentation. The conclusion of this study is that the promotion strategy using digital marketing has been implemented by pia business people in Pia Gempol Village. The social media used for product promotion are WhatsApp, Instagram, and Facebook. Businessmen also use Google My Business and Google Maps in m ark eting the products they sell. Constraints in the applicationofdigitalmarketing as a promotional strategy used by business actors are the most experienced by inadequate hum an resources in content creation. The b enefit of im plem enting digital m arketing as a prom otional strategy is that sales have increased, helping to facilitate prom otion and wider reach.